The Impact on Health Insurance Affordability for Maine Households If Enhanced Tax Credits Expire - Rhodes, Jordan; Schneider, Hilary (Maine Policy Review, 2025)
The Patient Protection and Affordable Care Act established premium tax credits to help eligible households lower their payments for qualified health plans offered through the health insurance exchanges. In 2021, Congress increased and expanded eligibility for these tax credits; however, without Congressional action, the enhanced tax credits will expire at the end of 2025. Using recent open enrollment data from Maine, this study examines the impact on Maine consumers if these enhanced tax credits expire. Without enhanced tax credits, average monthly premiums would have increased by 165 (59 percent) across Maine households in 2025. The impact is most pronounced among households in isolated rural areas where average monthly premiums would have increased by 175 per month (63 percent) without enhanced tax credits in 2025. Marketplace consumers in isolated rural areas may be especially vulnerable to higher premium costs given the aging demographic profile and relatively high rates of self-employment in fishing and lobstering in these communities.